Development and oxidative stability of pistachio (Pistacia vera L.) spread - Shakerardekani, Ahmad (2012)
Pistachio nut (Pistacia vera L.) is one of the popular tree nuts in the world. Due to its high nutritional value, pistachio is an increasingly important nut consumed either in the form of raw, roasted or salted. The main objective of this study was to value-add pistachio nut (Ohadi variety) by conversion into an acceptable and shelf-stable pistachio spread. Specifically, this study was conducted to investigate the effect of processing conditions of pistachio kernels (roasting and milling) on the quality of pistachio paste, to develop pistachio spread as a new product, and to determine the physicochemical properties and oxidative stability of pistachio spread. In the first part of the study, results obtained showed that increases in roasting temperature and time caused a decrease in the color attributes of both whole kernels and ground kernels except for the a value of ground kernels. The hardness (N) and color attributes (L value, b value and yellowness index) of whole kernels and the 'a' value of ground kernels could be used to monitor the roasting quality of whole kernels. The recommended range of roasting temperature and time of whole kernels for the production of pistachio paste were 130-140°C and 30-40 min, respectively. The colloidal stability of pistachio paste samples was found to be influenced by particle size and the most stable pistachio paste was obtained when the mill gap size was 20 μm. All pistachio pastes under study depicted the pseudo-plastic and thixotropic behaviors. The Herschel-Bulkley model was the most appropriate model to describe the flow behavior of pistachio paste. The storage modulus (G') values of pistachio paste were higher than the loss modulus (G'') values for all frequencies studied. The second part of this study concentrated on the development of pistachio spread from the pistachio paste. The spread was prepared using pistachio paste as the main component, icing sugar, soy protein isolate and red palm oil at different ratios. A total of 17 formulations were prepared. From the study, two formulations were selected based on their sensory properties, work of shear, color attributes, oil stability, flow behavior and dynamic oscillatory property. The two formulations were Formulation 12 which contained 50.0% pistachio paste, 30.0% icing sugar, and 20.0% red palm oil, and Formulation 16 which comprised of 58.3% pistachio paste,25.0% icing sugar and 16.7% red palm oil. Following this, appropriate terminologies for describing the sensory characteristics of these pistachio spreads were developed using quantitative descriptive analysis (QDA). Thirty-two potential panelists were screened and only twelve panelists were selected for training and finally only eight of them were found to be qualified for the evaluation of pistachio spread. Twenty attributes in terms of appearance, aroma, flavor, texture and aftertaste of pistachio spread were identified and developed by the trained panelists. Results from sensory evaluation showed that no significant (P < 0.05) difference was observed in all the sensory attributes between the selected pistachio spread formulations except for sweetness. In the third part of this study, further improvement of the pistachio spread, especially with respect to prevent oil separation, was made by the addition of monoglycerides (Dimodan HP-M). Results showed that the addition of 0.75 and 1.5% of monoglycerides led to the reduction in oil separation during storage probably due to creation of a strong network between fat, protein and other component by the emulsifier. The addition of monoglycerides also influenced the rheological characteristics such as the flow behavior (K, n, A, τ0 and R), dynamic oscillatory values (Gʹ, Gʹʹ and tan δ) and color of the spread. The most suitable formulation based on the observed physicochemical, physical and rheological studies was the one that contained 58.3% pistachio paste, 25.0% icing sugar, 15.2% red palm oil and 1.5% monoglycerides. Based on the results obtained on the effect of accelerated storage at 60oC, it can be concluded that the shelf life of pistachio spread was 320 days at 20 ± 2°C.